Use of Pneumococcal Disease Epidemiology to Set Policy and Prevent Disease during 20 Years of the Emerging Infections Program - Moore, Matthew R. (Emerg Infect Dis, 2015)
Two decades ago, the Emerging Infections Program of the US Centers for Disease Control and Prevention implemented what seemed like a simple yet novel idea: a population- and laboratory-based surveillance system designed to identify and characterize invasive bacterial infections, including those caused by Streptococcus pneumoniae. This system, known as Active Bacterial Core surveillance, has since served as a flexible platform for following trends in invasive pneumococcal disease and studying vaccination as the most effective method for prevention. We report the contributions of Active Bacterial Core surveillance to every pneumococcal vaccine policy decision in the United States during the past 20 years.